LATIHAN PUSH UP DAN PULL UP TERHADAP PENINGKATAN POWER OTOT LENGAN PADA PEMAIN VOLI - Febriani, Yelva; Adenikheir, Annisa; Zahara, Tazkya (Prodi Fisioterapi UFDK, 2024)
ABSTRACTPower is a movement ability that is very important to support activities in every branch of sport. This power or explosive ability will determine good movement results. Power concerns the strength and speed of dynamic and explosive muscle contractions and involves the maximum expenditure of muscle strength in the shortest possible time. This study aims to determine the effect of push up and pull up exercises on increasing arm muscle power in volleyball players. This type of research is quantitative which uses a quasi-experimental research design. The sample collection technique uses the purposive sampling method. This type of research is a quasi experimental one group pre-post test design, this research was carried out 12 times with 1 rest per exercise for 10 samples. Increased arm muscle power is measured by performing a Service Test. The research results from giving push up and pull up exercises showed that the average arm muscle power before the intervention was 15.30 and after the intervention it increased to 19.90. The P value <a= (0.000) means that there is an influence on increasing arm muscle power. From the research results, it can be concluded that there is an influence before and after giving push up and pull up exercises on increasing arm muscle power in volleyball players.References: 27 (2011-2023)Keywords: Power, Push Up, Pull Up